The Comprehensive Systematic Review of Impact of Early Mobilization on Long-term Outcomes in ICU Patients - Mohamad Fadli; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2026)
Introduction: Early mobilization in intensive care unit (ICU) patients has been proposed to mitigate the deleterious effects of critical illness, yet its impact on long-term outcomes remains uncertain. This systematic review comprehensively evaluates the effects of early mobilization on long-term functional, cognitive, quality of life, and healthcare utilization outcomes in adult ICU patients. Methods: A systematic review was conducted following PRISMA guidelines. We included randomized controlled trials, controlled clinical trials, cohort studies, case-control studies, systematic reviews, and meta-analyses involving adult ICU patients (≥18 years) who received early mobilization (initiated within 72 hours of ICU admission or mechanical ventilation) compared to standard care or delayed mobilization. Long-term outcomes were defined as those measured at least 30 days post-ICU or hospital discharge. Data were extracted on patient characteristics, mobilization protocols, long-term outcomes, safety, and study quality. Results: Sixty-eight studies were included, comprising over 30,000 patients. Early mobilization consistently improved short-term functional outcomes, including muscle strength (mean difference 4.47-8.62 points on MRC scale), reduced ICU-acquired weakness (OR 2.04-2.7 for independent functional status), and increased likelihood of walking independently at discharge (OR 2.13) (Patel et al., 2023; Tipping et al., 2017; Hu et al., 2019). However, large randomized controlled trials found no significant improvement in long-term mortality (Hodgson et al., 2022) or quality of life at 6-12 months (Higgins et al., 2025). Notably, one trial demonstrated reduced cognitive impairment at 1 year (24% vs 43%, p=0.0043) (Patel et al., 2023). Subgroup analyses revealed potential harm in diabetic patients receiving high-intensity mobilization (adjusted OR 3.47 for 180-day mortality) (Serpa Neto et al., 2024). Adverse event rates were low (<3%), though the TEAM trial reported more events in the intervention group (9.2% vs 4.1%, p=0.005) (Hodgson et al., 2022). Discussion: The evidence presents a complex picture where early mobilization yields clear short-term functional benefits that do not consistently translate into improved long-term survival or quality of life. Heterogeneity in protocols, patient populations, and outcome measures limits definitive conclusions. Conclusion: Early mobilization safely improves in-hospital functional outcomes and reduces healthcare utilization. However, long-term benefits beyond hospital discharge remain unproven, and high-intensity protocols may harm specific subgroups. Individualized, progressive mobilization strategies are recommended.